A Multidimensional and Longitudinal Exploratory Study of the Stability of Pregnancy Contexts in the United States - Melissa A. Markowitz; Lisbet S. Lundsberg; Aileen M. Gariepy (Mary Ann Liebert, 2024)
Objective: Evaluate the longitudinal stability of six pregnancy contexts, including intention, in a diverse cohort of individuals experiencing delivery, abortion, or miscarriage. Methods: We enrolled individuals 16?44 years of age with pregnancies <24 weeks gestation in this longitudinal study between June 2014 and June 2015 in four US urban clinics. We assessed six pregnancy contexts (intention, wantedness, planning, timing, desirability, and happiness) at enrollment and 3-month follow-up. We constructed three-level categorical measures for each context defined as favorable, ambivalent, or unfavorable. We used Wilcoxon sign tests to evaluate changes in paired observations between pregnancy context measures over time and by pregnancy outcome. Results: Among 121 participants at median gestational age of 7 weeks and 3 days, we found intention, wantedness, planning, timing, and happiness remained unchanged from enrollment in early pregnancy to 3-month follow-up. Individuals demonstrated changes in desirability; pregnancy assessments shifted toward less desirable from enrollment to follow-up (p?=?0.01) (i.e., desired to ambivalent, or ambivalent to undesired). Among participants choosing delivery (57%), assessments shifted toward more favorable planning (i.e., unplanned to ambivalent, or ambivalent to planned) (p?<?0.01), and less favorable desirability (i.e., desired to ambivalent or ambivalent to undesired) (p?<?0.01) at follow-up. Among participants choosing abortion (28%), assessments shifted toward more unfavorable planning (i.e., planned to ambivalent, or ambivalent to unplanned) at follow-up (p?<?0.01). Conclusion: In multidimensional, longitudinal assessment, pregnant participants' perspectives on five of six pregnancy contexts remained unchanged between enrollment and 3-month follow-up; only desirability shifted. Pregnancy planning perspectives differed by pregnancy outcome. Human Research Subjects Protection Program: 1310012926.